BLACK PRETERM BIRTH RISK IN NON-BLACK NEIGHBORHOODS: EFFECTS OF HISPANIC, ASIAN, AND NON-HISPANIC WHITE ETHNIC DENSITIES - Mason, Susan M. (2011)
PURPOSE: Studies of ethnic density and health in the United States have documented poorer health outcomes in black compared to non-black neighborhoods, but few studies have considered the identities of the non-black populations. METHODS: New York City birth records from 1995 through 2003 and a spatial measure of ethnic density were used to examine preterm birth risks among non-Hispanic black women associated with non-Hispanic white, Hispanic, Asian, and non-Hispanic black neighborhood densities. Logistic regression models were used to estimate the effect on black preterm birth risks of replacing white neighbors with Hispanic, Asian, and black neighbors. Risk differences were computed for changes from the 10(th) to the 90(th) percentiles of ethnic density. RESULTS: Increasing Hispanic density was associated with reduced preterm birth risks among non-Hispanic black women, especially if the black women were foreign-born (RD=−19.1 per 1,000 births; 95% CI: −28.6, −9.5). Estimates for increasing Asian density were null. Increasing black density was associated with increasing black preterm birth risk, with a threshold at higher levels of black density. CONCLUSIONS: The low risks of preterm birth among foreign-born non-Hispanic black women in majority-Hispanic neighborhoods may be related to protective psychosocial or nutritional factors in Hispanic neighborhoods.